ANALYSIS OF GRANITE ROCK WEATHERING IN THE PARMONANGAN AREA USING LANDSAT 8 SATELLITE IMAGERY (EINSTEIN (e-Journal), 2024)
A research has been conducted to analyze the weathering of granite rocks in the Parmonangan area using Lansat 8 satellite imagery which aims to determine the distribution of rocks, weathering processes, and types of rock forming elements in Parmonangan District, North Tapanuli Regency. The method used is using shp geologic map data and Lansat-8 image data processed using Arcgis Map 10.6.1 to determine the distribution of rocks and land cover. XRF is used to identify compounds and rock-forming elements. The results obtained by the rock distribution of the parmonangan area are in the form of the Kluet Formation, Sibolga Complex and Toba Tuff. Land cover in the parmonagan area has differences from 2016 to 2024. Open land in 2024 has increased and the cloud cover obtained has also increased. The rock elements found are Al2O3 (25.31), SiO2 (24.97), K2O (1.56), TiO2 (0.81), Mn2O (30.66), Fe2O3 (4.66), ZrO2, (0.21), Sb2O3 (0.16), and BaO (0.17).
Keywords: Weathering; Land Cover; XRF; Granite; Parmonangan